Parameter misspecification and robust monetary policy rules - Carl E. Walsh (European Central Bank (ECB), 2005)
In this paper, I evaluate the performance deterioration that occurs when the central bank employs an optimal targeting rule that is based on incorrect parameter values. I focus on two parameters — the degree of inflation inertia and the degree of price stickiness. I explicitly account for the effects of the structural parameters on the objective function used to evaluate outcomes, as well as on the model's behavioral equations. The costs of using simple rules relative to the costs of parameter misspecification are also assessed.
Keywords: E52; E58; 330; Misspecification; monetary policy; Robustness; Geldpolitik; Regelbindung versus Diskretion; Neoklassische Synthese; Robustes Verfahren; Modellierung